Anti-intellectualism in Wang Mingdao’s Fundamentalist Theology - Muzhi GE (Journal of Research for Christianity in China (JRCC), 2024)
The problem of anti-intellectualism in the Chinese Church has received increasing attention from scholars, but so far no article or book has investigated the anti-intellectualism in the thought of Wang Mingdao. In fact, just as Watchman Nee’s trichotomous view of humanity has left a profound anti-intellectual impact on the Chinese Church, so is Wang Mingdao’s fundamental theology an essential part of the Chinese church’s anti-intellectual tradition. To better understand the origins of anti-intellectualism in the Chinese Church, this paper will examine how Wang Mingdao’s fundamentalist theology is foundational to his anti-intellectual thought.